Visual search with animal fear-relevant stimuli: A tale of two procedures - Waters, A.; Lipp, Ottmar; Randhawa, R. (2011)
The present study assessed preferential attentional processing of animal fear-relevant stimuli in two procedures, Search and Interference tasks, which have been suggested to reflect on attentional capture due to the fear-relevance of the stimuli presented. In the Search task, participants (N = 154) searched fear-relevant (i. e., snakes and spiders) and non fear-relevant (i. e., fish and birds) backgrounds to determine the presence or absence of a deviant animal from the opposite category. In the Interference task, the same participants searched for the presence or absence of a neutral target (a cat) when either a snake, spider or no distracter were embedded amongst backgrounds of other animal stimuli. Replicating previous findings, preferential attentional processing of animal fear-relevant stimuli was evident in both procedures and participants who specifically feared one animal but not the other showed enhanced preferential processing of their feared fear-relevant animal. However, across the entire sample, there was no relationship between self-reported levels of animal fear and preferential processing which may reflect on the fact that substantial preferential attentional processing of fear-relevant animals was evident in the entire sample. Also, preferential attentional processing as assessed in the two tasks was not related. Delayed disengagement from fear-relevant stimuli appeared to underlie performance in the search task but not in the interference task. © 2010 Springer Science+Business Media, LLC.